1986
DOI: 10.1111/j.1469-8137.1986.tb00622.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF MYCORRHIZAL INFECTION ON PLANT GROWTH, NITROGEN AND PHOSPHORUS NUTRITION IN GLASSHOUSE‐GROWN ALLIUM CEPAL.

Abstract: SUMMARYGrowth and rates of uptake of nitrogen and phosphorus (inflow) in Allium cepa L. were measured in three experiments. EfTects of mycorrhizal infection {Glomus mosseae (Nicol. and Gerd.) Gerdemann and Trappe) and N and P fertilization were investigated. The experiments were carried out in a naturally-lit glasshouse, so that seasonal variations in solar radiation infiuenced experimental results.In all experiments, a large positive growth response to mycorrhizal infection was observed when soil P was low. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 31 publications
3
43
0
2
Order By: Relevance
“…The outcome will relate to root growth rates, root length density and propagule density, and hence the chance of a propagule hitting a root (Smith et al 1986). However, the fact that percentage colonisation in each pot size was similar for the two cultivars, despite large differences in root length and specific root length suggests that propagule density was sufficient to achieve maximum colonisation in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome will relate to root growth rates, root length density and propagule density, and hence the chance of a propagule hitting a root (Smith et al 1986). However, the fact that percentage colonisation in each pot size was similar for the two cultivars, despite large differences in root length and specific root length suggests that propagule density was sufficient to achieve maximum colonisation in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…P uptake was found to be positively correlated with root length in high-P soil, but not in low-P soil or in soil where volume was limited (Otani and Ae 1996). Responsiveness of host plants to AMF colonisation is sensitive to soil P availability (Smith and Read 1997), and hence possibly to soil volumes of experimental pots. Facelli et al (1999) have shown that the higher the plant density (relatively small soil volume per individual plant) the lower the mycorrhizal responsiveness.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another consideration to improve downy brome and Japanese brome control and enhance reclamation involves arbuscular mycorrhizal fungi (AMF), which significantly aid the growth and development of mycorrhizal plants (Allen and Allen 1984;Killham 1985;Read et al 1985;Smith et al 1986;Trappe 1981). Downy brome is a facultative mycorrhizal plant and does not have to develop such an association to survive or even dominate a site (Pendleton and Smith 1983;Trappe 1981).…”
Section: Other Cultural Considerationsmentioning
confidence: 99%
“…AMF play a vital role n the mineral nutrition of host plants (Trappe 1981) and increase the amounts of accumulated macro-and micronutrients (Killham 1985;Read et al 1985;Smith et al 1986). Additionally, AMF colonization of herbaceous species improved drought tolerance (Allen and Allen 1984;.…”
Section: Downy Brome and Soil Symbiontsmentioning
confidence: 99%